Quantificação da biomassa e nutrientes em uma floresta estacional decidual em Itaara-RS, Brasil - Vogel, Hamilton Luiz Munari (2005)
This study was conducted in a farm belonging to Military Brigade in the Itaara county, RS. The main objective was to quantify the nutrient stocks in the soil and the above ground biomass. The second aim was to evaluate the litterfall from different tree species, and to quantify the internal nutrient cycling and the nutrient flux to the soil, respectively. The total contents of N, P, K, Ca, Mg, S, Fe and Mn were determined for all plant and soil material. For sample collection 8 trenches were opened. Soil samples were taken in each 10 cm depth for determining soil density and the chemical analysis of total and available nutrient contents. To litter collection six plots (25 m x 17 m) were marked with five round collectors in each plot. Litter collections were done monthly, during a period of 24 months. The litter material was separated in the laboratory in leaves, fine branches (< 1 cm) and miscellaneous (flowers, fruits, seeds and debris of unidentified plants). After this preseparation a further separation followed selecting the leaves of 7 tree species. To quantify the biomass, the trees were separated in the fractions stemwood, stembark, branches and leaves. The biomass estimation based on the equation log y = b0 + b1 . log DAP, which was derived from the biometric data. The results indicate that the soil of the studied area has a medium fertility. In the 24 months of litter collection the main deposition occurred in the beginning of winter and spring. The leaves contributed with 72% in litter composition, the fine branches with 16%, and the miscellaneous with 12%. There wasn t a significant correlation between the climatic variables (average temperature and monthly rainfall) and the litterfall. Great amounts of nutrients are allocated in the litter being an important way of internal nutrient cycling within the forest. Parapipdania rigida was the species with the greates cycling rate along the 24 months. In total the following increasing order exists: Parapipdania rigida > Ocotea pulchella > Matayba elaeagnoides > Ocotea puberula > Nectandra megapotamica > Schinus mole > Cupania vernalis. The highest contents of N, P, and Ca were found in Parapipdania rigida, the highest contents of K, Mg and S were found in Matayba elaeagnoides. The above ground biomass totaled to 210 Mg ha-1. Branches had the greatest amount followed by stemwood > stembark > leaves. However, the highetst contents of N, P, K, Mg and S were found in the leaves, the highest Ca contents in the stembark. Compared with the other tree compartments branches had the highest stock of nutrients. More than 55% of total N, P, K, Ca, Mg and S of the above ground biomass was stored in this compartment. Regarding to the total forest ecosystem the highest stocks of N, P, K, Ca, Mg and S are in the soil. In view of a potential usage a complete removal of stemwood and wood branches would cause an essential export of N, P, K, Ca, Mg and S. However, if harvesting is restricted to stemwood, only 19% N, 21% P, 25% K, 17% Ca, 28% Mg and 29% S would be removed outside the environment. More than 70% of the nutrients will remain in the ecosystem.